PRADO MUSEUM - SUCCESSFUL MODEL FOR RAISING COMPETITIVENESS IN THE ROMANIAN CULTURAL ORGANIZATIONS IN THE CONTEXT OF URBAN DEVELOPMENT - Răzvan-Andrei CORBOȘ; Ruxandra-Irina POPESCU (Management & Marketing)
The interest in the conceptual delimitation of the competitiveness of cultural organizations, as well as in identifying the sources of its growth, has increased in recent years due to the need to diversify the funding sources of this type of organization, urban development and the willingness to adapt to the requirements of customers who are more numerous and have diverse expectations. Practice shows that cultural organizations that have adopted a competitive economy vision and have applied specific management tools for increasing the organizational competitiveness, have achieved a good performance, becoming, this way, an example of managerial success story in the field. The experience of Prado Museum, one of the emblems of Madrid, falls in this direction. The substantial increase in the number of tourists, the decrease in state funding combined with the increase of proprietary financing resources, the enhancement of the national and international reputation, are just some of the positive results that prove the quality of used management. This paper presents and analysis these effects and the causes that have generated them, thus providing some possible suggestions for action for Romanian cultural organizations in order to increase their competitiveness.